Long-term interest rate spillovers from major advanced economies to emerging Asia - Ansgar Belke; Irina Dubova; Ulrich Volz (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
This paper explores the extent to which changes to long-term interest rates in major advanced economies have influenced long-term government bond yields in Emerging Asia. To gauge long-term interest spillover effects, the paper uses VAR variance decompositions with high frequency data. Our results reveal that sovereign bond yields in Emerging Asia responded significantly to changes in US and Eurozone bond yields, although the magnitudes were heterogeneous across countries. The magnitude of spillovers varied over time. The pattern of these variations can partially be explained by the implementation of different unconventional monetary policy measures in advanced countries. – – In diesem Papier wird untersucht, inwieweit die Änderungen der langfristigen Zinsen in den großen fortgeschrittenen Volkswirtschaften die langfristigen Staatsanleiherenditen der asiatischen Schwellenländer beeinflussen. Um langfristige Zinsübertragungseffekte zu messen, verwendet das Papier VAR-Varianzzerlegungen mit Daten hoher Frequenz. Unsere Ergebnisse zeigen, dass Staatsanleiherenditen in asiatischen Schwellenländern deutlich auf die Veränderungen der Anleiherenditen der USA und der Eurozone reagierten. Dabei fielen die Größenordnungen in den einzelnen Ländern allerdings nicht einheitlich aus. Das Ausmaß der Spillovers variierte zudem im Zeitablauf. Das Muster dieser Variationen kann teilweise durch die Implementierung verschiedener unkonventioneller geldpolitischer Maßnahmen in fortgeschrittenen Ländern erklärt werden.
Keywords: E52; E58; F42; 330; Long-term interest rates; bond yields; monetary policy spillovers; Emerging Asia